Studi Kualitatif Deskriptif Tentang Pemahaman Mahasiswa Sekolah Tinggi Teologi Soteria Purwokerto Mengenai Dosa - Yaudi Santos Santoso (Voice, 2024)
This study was to determine the understanding of Soteria Purwokerto Theological College students about sin. To know the biblical affirmation of facts and symptoms as well as the resolution of sin in human life. This study uses a descriptive qualitative research design in the study of biblical theology. Questionnaire questions are used as a source of information to obtain data directly from the source. The data collected will be analyzed to find solutions to problems and find conclusions to answer research problems. The results and findings reveal that sin a violation of God’s law. Break up with God. Sin is destructive and results in death. The solution and resolution of sin is God’s work through Jesus Christ which is received through the gift of the new birth, which is followed by repentance and faith as the response of the born again to enjoy eternal life and grow up as God’s children who are more like Jesus Christ.